ENHANCING EDUCATION QUALITY THROUGH INTERNAL QUALITY ASSURANCE STRATEGIES - Suyanto Suyanto; Yetty Faridatul Ulfah (Profetika: Jurnal Studi Islam, 2024)
The objective of this study is to 1) assess methods for enhancing educational quality via internal quality assurance, and (2) evaluate the effects of internal quality assurance within the Muhammadiyah Middle School (SMP) of Special Program at Kottabarat, Surakarta. This qualitative research was conducted at the Muhammadiyah Middle School Special Program at Kottabarat, Surakarta in December 2023. The research design used a descriptive approach with a phenomenology. Data collection techniques applied interviews, documentation and observation. The findings of this study reveal that (1) the approach to enhancing educational standards through internal quality assurance at SMP Muhammadiyah of Special Program at Kottabarat, Surakarta involves a systematic process established by the educational institution. This process is designed to regulate and enhance educational standards, guided by governmental regulations and the distinctive characteristics of Muhammadiyah education. The steps involved in ensuring educational excellence include quality mapping, planning, organization, implementation, evaluation, and subsequent follow-up. (2) The implementation of internal quality assurance at SMP Muhammadiyah of Special Program at Kottabarat, Surakarta, has led to improvements in both academic and non-academic realms. These improvements have resulted in heightened public confidence in the school and enhanced services provided to students and parents.